2016
DOI: 10.1016/j.kjms.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Can immediate second resection be an alternative to standardized second transurethral resection of bladder tumors?

Abstract: This study analyzed the impact of an immediate second transurethral resection of bladder tumor (TURBT) protocol on residual tumor status at the initial TURBT session and the recurrence rate in the primary resection area. We prospectively evaluated and randomized 47 consecutive patients who underwent TURBT sessions for bladder cancer. In accordance with the inclusion criteria, of the 47 consecutive patients, 19 (Group I) underwent immediate second resection of the tumor bed after complete TUR and 28 (Group II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…(B) The short-term progression-free survival of TUR plus EBCA was better (HR, 0.19; 95% CI, 0.05-0.65; log-rank p = .003) it was reported that residual tumor cells covered by extracellular matrix could be resistant to adjuvant chemotherapy and BCG. 22 Therefore, we believe that patients with high-risk NMIBC will still benefit by LC of the disease from SI, although it might be dampened by adjuvant therapies. A similar result showed that high-risk NMIBC patients might get few benefits from SI.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…(B) The short-term progression-free survival of TUR plus EBCA was better (HR, 0.19; 95% CI, 0.05-0.65; log-rank p = .003) it was reported that residual tumor cells covered by extracellular matrix could be resistant to adjuvant chemotherapy and BCG. 22 Therefore, we believe that patients with high-risk NMIBC will still benefit by LC of the disease from SI, although it might be dampened by adjuvant therapies. A similar result showed that high-risk NMIBC patients might get few benefits from SI.…”
Section: Discussionmentioning
confidence: 98%
“…Upstaging occurred in 0% to 8% (Ta to ≥T1) and 0% to 32% (T1 to ≥T2) of patients. In one RCT, an immediate ReTUR was performed by another urologist and the residual tumor rate was 10.5% 22 . To improve the efficacy of TUR, attempts have been made to improve surgical techniques and adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations